CRISPR/Cas12a Powered DNA Framework‐Supported Electrochemical Biosensing Platform for Ultrasensitive Nucleic Acid Analysis (Small Methods 12/2021). Issue 12 (13th December 2021) - Su, Jing; Ke, Yuqing; Maboyi, Nokuzola; Zhi, Xiao; Yan, Sijia; Li, Fuwu; Zhao, Bo; Jia, Xiaolong; Song, Shiping; Ding, Xianting
Abstract : Front Cover In article number 2100935, Song, Ding, and co‐workers have developed a CRISPR/Cas12a powered DNA framework‐supported biosensing platform via cleavage of Cas12a on the heterogeneous electrochemical interface. The 3D tetrahedral framework nucleic acids would improve and expand the application of CRISPR/Cas's technology to the electrochemical interface‐based nucleic acids analysis.